Application of Structural Conditionality : 2008 Annual Report. (Policy Papers; Policy Paper ;, 2008)
This report provides an update, based on objective indicators, of the application of structural conditionality in Fund-supported programs. Such annual reports on structural conditionality are one element of the management implementation plan (MIP) prepared in response to the Board-endorsed recommendations made in the IEO evaluation of Structural Conditionality in IMF-Supported Programs. This annual report covers Fund arrangements approved during the period 1995-2007 (and their reviews through April 30, 2008), extending therefore the dataset contained in the recent IEO report by about three years (from 2005 to 2007). In addition, this report examines experience with Policy Support Instruments (PSIs), which were introduced in October 2005, and thus not covered in the IEO evaluation.